Counter-terrorism international law and practice - De Frias, Ana Maria Salinas; Samuel, Katja LH; White, Nigel D. (Oxford University Press, 2012)
Government responses to terrorism can conflict with the protection of human rights and the rule of law. By comprehensively looking at all aspects of counter-terrorism measures from a comparative perspective, this book identifies best practices and makes clear recommendations for the future